Campamentos mineros en el Perú: Análisis bioclimático y recomendaciones de diseño para mejorar el confort interior. - Arispe Sevilla, Fiorella Silvana; Vera Piazzini, Ofelia Giannina (Revista: Módulo Arquitectura CUC)
The study analyzes the behavior of three Peruvian mining camps in response to specific climatic and geographic variables with the objective of determining guidelines and criteria for bioclimatic architectural design, which seek to improve the quality of life, comfort and safety of the mining worker. The analysis was carried out through three study cases located in two climatic zones of Peru: Desert (BW) and Mesoandina (Dwb). The studied camps belong to large mining projects and are located within the area of influence of the mining operation. Objective and subjective evaluations were used: data collection in situ, digital simulations, surveys and user interviews. The research has made it possible to identify the main variables that influence the thermal, acoustic and lighting behavior and to propose design recommendations that can be implemented to improve the comfort of the studied cases, as well as future projects with similar climatic conditions.